Awareness about Community Management of Hyperglycemia during Pregnancy among Medical Undergraduates in Western Uttarakhand - Mishra, Surabhi; Sharma, Neha; Srivastava, Abhay; Semwal, Jayanti; Joshi, Anamika; Gupta, Kezia (Indian Journal of Community Health, 2024)
Background: All women with hyperglycemia in pregnancy (HIP) require optimal care. With western Uttarakhand alone recording a HIP prevalence of 9.7%, the successful implementation of HIP guidelines pan-India at primary healthcare level becomes paramount. Aim and objective: The present cross-sectional study aimed to assess the baseline awareness of medical undergraduates regarding HIP management protocols assuming higher their knowledge better the successful implementation of these guidelines within the community. Methodology: A descriptive study was carried out among 309 medical undergraduates at a private teaching institute in Uttarakhand. Data was collected using a self-administered, pre-tested questionnaire. Based on individual knowledge scores, participants were subdivided into: good (score?24), moderate (score 12-24), and poor (score<12) knowledge categories. Data were analyzed using Statistical Package for Social Sciences. Results: Most subjects (92.2%) reported reading Indian textbooks on obstetrics; despite this, only 3.6% of subjects had good awareness of the protocols. Sub-domain analysis showed while 90.0% of respondents had a fair understanding of the disease basics, more than two-thirds lagged in recollecting its standard diagnostic and management protocols including the role of health workers. Conclusion: Most medical undergraduates have overall poor-to-moderate awareness of HIP management especially the diagnostic and management protocols including the role of health workers.